The effect of a persuasive information campaign on students' intention to save water - Azaki, Joshua Ishaku (Department of Information Systems, 2021)
The City of Cape Town (CoCT) experienced three years of drought, which led to the implementation of several water demand management (WDM) strategies by the management of the University of Cape Town (UCT) to facilitate efficient water-saving behaviours among water users. The goal of the WDM strategies was to reduce the rate of water consumption by up to 50% of the regular use. This study implemented a Persuasive Information Campaign (PIC) in four UCT student residences selected on the criteria that they had a smart meter. This study aimed to examine if a PIC disseminated through Short Messaging Service (SMS), email and both SMS and email could increase students' intention to save water. The use of the different channels was to test the effectiveness of each on students' intention to save water. The extended Theory of Planned Behaviour (TPB) was used as a theoretical model to guide the study in achieving its aim. The main constructs of the theory are attitude (a positive or negative evaluation of the benefits of performing a behaviour), social norms (an individual's social perception of performing a behaviour), perceived behavioural control (how easy or difficult performing a behaviour is), and intention to save water (how hard students are willing to try and how much effort they are planning to exert to save water). The additional constructs added to the theory were PIC (a persuasive message advocating for less water consumption by students), knowledge about the need for water-saving (students' perception about water-saving), and exposure to information about water crisis (sources and channels of information about water crisis). A total of 145 questionnaire responses were collected and analysed using the Partial Least Square Path Modelling (plspm) package in R software. The factor loading results from the data analysis showed that students who received the PIC by both SMS and email channel were the most persuaded to increase their intention to save water. While the students who received the PIC through SMS only was the next persuaded. The students who were least persuaded by the PIC were the ones who received the PIC by email only. The overall analysis revealed three main predictors of student's intention to save water, and these include students' knowledge about the need for water-saving (strong positive effect), attitude towards water-saving (strong positive effect), and perceived behavioural control vii (marginal positive effect). These results suggest that the more positive students' attitudes are towards water-saving, and the more knowledgeable they are about water-saving, the higher their intention to save water will be. Although PIC was not among the predictors of students' intention to save water, it had a strong positive effect on students' attitude towards water-saving. This effect also suggests that PIC is important in achieving attitudinal change among students. This study is the first study conducted using PIC as a new construct added to TPB and in the context of a higher institution of education.